A comparison between fatwa in Malaysia and Indonesia in muamalat / Ahmad Husaini Abd Karim … [et al.] - Mahamod, Jalaluddin; Sh Abdul Halim, Sh Mohd Ashaari; Ruslan, Muhammad Fauzan; Abd Karim, Ahmad Husaini (2023)
Muamalat in general is a relationship between humans and humans, especially muamalat related to property such as the concept of property, ownership theory, contracts, buying and selling, companies, waqf, investments and mortgages. However, it is not widely written and studied in Malaysia because the rapid development only happened after Islamic banking was offered in 1983. However, writing in the form of fiqh has been approved by writers and researchers since long ago. This paper is a content analysis study (content analysis) involves previous writing and research, especially related to fatwa muamalat in Malaysia. The trend of writing and research related to muamalat and fatwa can be divided into two eras, namely before and after Islamic banking was established, which is in 1983.